Dealing with english writing skills: Through the eyes of vocational students - Siregar, Sari Putri Elrida; Sari, Fiska; Sudjoko, Sudjoko; Yundayani, Audi (Eureka: Journal of Educational Research, 2022)
Students in vocational programs must have English writing abilities, following industry standards. Despite this, writing is a challenging skill. This article examines the voice of vocational students in connection to their English writing proficiency. Sixty-one students from a private vocational school are involved in the research. This study was designed as descriptive research. Data on students' voices are collected using a questionnaire and a semi-structured interview. Additionally, they are evaluated utilizing triangulation techniques. According to the research, the majority of students continue to struggle with communicating their thoughts in writing. In addition, they struggle to organize their sentences into paragraphs. Moreover, their knowledge of grammar and vocabulary is weak, as is their understanding of writing mechanisms. These conditions decrease their motivation to participate in the writing process actively. It is vital because vocational students should be the source of industrial employment. Therefore, the English teacher is strongly urged to develop a lesson plan that considers the students' requirements, profiles, and prior writing skills, using need analysis and diagnostic evaluation. In addition, it is strongly recommended that students engage in collaborative writing through any medium, including technology, to assist them. In addition, it is crucial to frequently assess the material in light of the industry's requirements for writing abilities competencies. The concept of differentiated teaching can also be employed to assist students' distinct development of writing skills.